Pengaruh Penerapan Marketing Mix terhadap Minat Nasabah Pada Investasi Emas di Bank Syariah Indonesia KCP Surabaya Diponegoro 2 - Kurniawati, Putri Aprilita (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Marketing Mix is a marketing activity that is integrated and mutually supports each other. This means that the marketing mix is used by the company to achieve its goals in the target market. Meanwhile, Sharia Marketing is a strategic business discipline that directs the process of creating, offering and changing value from an initiator to its stakeholders, which in the entire process is in accordance with the contract and principles of muamalah (business) in Islam. So, the purpose of this research is to measure the desires/interests of a customer based on interest in a gold investment product by implementing marketing carried out by employees. This research uses quantitative descriptive research methods. Research methodology is a rational, empirical and systematic way of scientific thinking used by researchers in a scientific discipline to carry out research activities. The results of this research show that: The implementation of the Marketing Mix at BSI KCP Surabaya Diponegoro 2 is included in the good category, as evidenced by the results of descriptive statistical analysis of 89% and customer interest in gold investment is also in the good category of 88%. Based on the T Test results, the calculated t value was 3.856 and the Sig. of 0.001. So, because the calculated t value > t table is 3.856 > 2.048 and the Sig. namely 0.001 < 0.05, then H0 is rejected and H1 is accepted, which means that partially there is an influence between (X) and (Y). Based on the R test results, the R Square value analysis results were 0.347. This value shows that the effect of implementing marketing mix on customer interest is 34.7%.